Aspects of Socioeconomic Exclusion in Kerala, India: Reflections from an Urban Slum - J. Devika (Critical Asian Studies, 2014)
This article probes the intersection of spatial, caste, and gender axes of power in shaping contemporary inequalities in Kerala, through mixed-method research in an urban slum. Relying largely on qualitative data, it constructs a history of work in the slum for lower caste men and women against the backdrop of Kerala politics from the 1940s until the present. It examines the role of widening gender gaps, the persistence of secularized caste, and flagging working-class politics and discourse in shaping contemporary socio-economic exclusion in urban areas.